Use of nanofluids for heat transfer enhancement in mixed convection - Öztop, Hakan Fehmi; Abu-Nada, Eiyad; Al-Salem, Khaled (CRC Press, 2015)
Mixed convection is a combination of natural convection and forced convection, where the Rayleigh number gives an indication to which mode of heat transfer is dominant. Mixed convection heat transfer can be observed in many engineering applications such as solar air collectors, heat exchangers, cooling of electronic equipments, and heating and cooling of buildings. © 2015 by Taylor & Francis Group, LLC.
Keywords: Electronic cooling; Mixed convection; Nanofluidics; Natural convection; Cooling of electronics; Engineering applications; Heat Transfer enhancement; Heating and cooling of buildings; Nanofluids; Rayleigh number; Solar air collector; Heat exchangers